Home and ambulatory blood pressure monitoring in children, adolescents and young adults: comparison, diagnostic agreement and association with preclinical organ damage. Issue 6 (June 2020) - Zeniodi, Maria Elena; Ntineri, Angeliki; Kollias, Anastasios; Servos, George; Moyssakis, Ioannis; Destounis, Antonios; Harokopakis, Angelos; Vazeou, Andriani; Stergiou, George S.
Abstract : Objectives: To compare the association of home (HBP), ambulatory (ABP) and office blood pressure (OBP) measurements with preclinical organ damage in young individuals. Methods: Individuals referred for elevated blood pressure and healthy volunteers aged 6–25 years were evaluated with OBP (2–3 visits), 7-day HBP and 24-h ABP monitoring. Organ damage was assessed by echocardiographic left ventricular mass index (LVMI), carotid ultrasonography [intima–media thickness (IMT)] and pulse wave velocity (PWV) using piezo-electronic or oscillometric technique. Results: Analysis included 251 individuals (mean age 14 ± 3.9 years, 70.9% men: 31.1% children, 54.6% adolescents, 14.3% young adults) of whom 189 had LVMI, 123 IMT and 198 PWV measurements. Office, ambulatory and home hypertension was diagnosed in 29.5, 27.1 and 26.3% of participants. The agreement of OBP with ABP was 74.5% (kappa 0.37) and HBP 76.1% (kappa 0.41), with closer agreement between HBP and ABP (84.9%, kappa 0.61). LVMI gave comparable correlations with systolic OBP, 24-h ABP and HBP ( r = 0.31/0.31/0.30, all P < 0.01). The same was the case for IMT (0.33/0.32/0.37, all P < 0.01) and piezo-electronic PWV (0.55/0.53/0.52, all P < 0.01), whereas oscillometric PWV gave stronger correlations with OBP than ABP or HBP. In linear regression analysis, the variation of LVMI was determined by night-time ABP, of IMT by HBP and of PWV by OBP and 24-h ABP. Conclusion: These data suggest that in young individuals, target organ damage is mainly determined by out-of-office rather than office BP. Home and ambulatory BP give comparable associations with preclinical organ damage.